Habermas e a educação: a práxis comunicativa no horizonte do pensamento pós-metafísico - Silva, Paulo Rogério da (Universidade Federal de São Carlos, 2014)
After identifying the interference of systemic mechanisms in education, reduced, in turn, to the utilitarian condition of simple means for the achievement of extrinsic ends, the dissertation presents the communicative praxis as a proposal of reflection and demarcation of the interests existing between system and culture. For this, it is taken into account the theoretical framework of Habermas, which guided by the paradigm of intersubjectivity, seeks to reintegrate a modern rationality and linguistically decentered (post-metaphysical), situated in the reality of procedural mode and based on the aspect dialogic performative of the interactions arising from the lived world. The communicative praxis, therefore, enables the enhancement of basic elements for democratic debate aiming the understanding , and then preventing the instrumental character of the unilateral coercions present in teaching procedures and, thus, to ensure learning that aims not only the logic of success, but also the experience of interactions permeated by cognitive, normative and aesthetic practices.
Keywords: Educação - filosofia; Práxis comunicativa; Mundo da vida; Mundo sistêmico; Pensamento pós-metafísico; Communicative praxis; Education; Life world; System world; Postmetaphysical thinking; CIENCIAS HUMANAS::EDUCACAO